Peran Konselor dalam Layanan BK dengan Teknik Self-Management untuk Meningkatkan Resiliensi Diri Siswa Kelas X MIA 5 di MA YPK Cijulang - Agung Jaelani; Elita Putri Melati; Osim Nuryana (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
This research aims to determine the role of counselors or guidance counselors in counseling services using self-management techniques to increase students' self-resilience so that they have the ability to identify and solve problems in students or those who experience stress due to academic pressure at school. Data collection in this research, literature study and qualitative research methods. The results of this research show that there are students who find it difficult to soive their personal problems and are not serious about taking learning. The role of the conselor is very necessary to guide student behaviour. The results of the research show that the role of conselors is in increasing the self-resilience of class X MIA 5 students at MA YPK Cijulang it is said to be effective because one of the setrategies used by Mrs. entang as by conducting group counseling on self-management techniques because according to him, by making students manage themselves, both in terms of feelings, actions and thoughts, this will really help the students become resilient people or people who can overcome whatever problems they face later.